Above Time: Rabbi Nachman's Tzaddik and Enlightened Temporal Experience. (17th June 2020) - Solomyak, Olla
Abstract: Rabbi Nachman of Bratslav describes the tzaddik (righteous person of spiritual enlightenment) as experiencing time in a distinctive, enlightened way: What is seventy years for the rest of us feels like a mere fifteen minutes for the tzaddik . Furthermore, even higher levels of enlightenment are possible—for a tzaddik on a higher level, what feels like seventy years for the first tzaddik is again but a mere fifteen minutes. This pattern continues, approaching a limit point which Rabbi Nachman calls "above time, " and which is the perspective on time of the Divine. How might Rabbi Nachman's claims about enlightened temporal experience be understood? In this paper, my aim is to examine some ways of understanding what it might mean to 'experience time more quickly' or to 'experience 70 years as 15 minutes' in light of contemporary theories of the structure of temporal experience. I then present a novel interpretation of Rabbi Nachman's claims which appeals to the contemporary notion of the specious present —a nonzero temporal interval experienced in a unified way as present .